Construction and Validation of a General Index for Job Demands in Occupations Based on ISCO-88 and KldB-92 - Kroll, Lars Eric (methods, data, analyses, 2011)
This paper describes the construction and validation of comprehensive scales for overall, physical and psycho-social job demands (ABges, ABphy, ABpsy) that were constructed using a large-scale representative survey from 2006 conducted by the German Federal Institute for Vocational Education and Training (BIBB). The overall goal is to provide comprehensive scales that can be applied in studies that are not able to measure job demands more thoroughly. The scales are based on standard occupational classifications. They were constructed using multi-level regression models in a three-stage procedure. The resulting index has been validated using seven different health indicators with the data of the German BIBB/BAuA-workforce survey and additional data of the GEDA: German Telephone Health Survey 2008/2009. Results indicated significant associations with health outcomes such as self-perceived health, perceived health risks at work or sick absence days. The index is free to use for scientific research and can be matched to any data source with data on occupations classified by KldB-92 or ISCO-88.